Advanced Differentiated Thyroid Cancer: A Complex Condition Needing a Tailored Approach - Antonio Mario Bulfamante; Eleonora Lori; Maria Irene Bellini; Elisa Bolis; Paolo Lozza; Luca Castellani; Alberto Maria Saibene; Carlotta Pipolo; Emanuela Fuccillo; Cecilia Rosso; Giovanni Felisati; Loredana De Pasquale (Frontiers in Oncology, 2022)
Differentiated thyroid cancers (DTCs) are slow-growing malignant tumours, including papillary and follicular carcinomas. Overall, prognosis is good, although it tends to worsen when local invasion occurs with bulky cervical nodes, or in the case of distant metastases. Surgery represents the main treatment for DTCs. However, radical excision is challenging and significant morbidity and functional loss can follow the treatment of the more advanced forms. Literature on advanced thyroid tumours, both differentiated and undifferentiated, does not provide clear and specific guidelines. This emerges the need for a tailored and multidisciplinary approach. In the present study, we report our single-centre experience of 111 advanced (local, regional, and distant) DTCs, investigating the rate of radical excision, peri-procedural and post-procedural complications, quality of life, persistence, recurrence rates, and survival rates. Results are critically appraised and compared to the existing published evidence review.